Wind properties of Milky Way and SMC massive stars: empirical Z dependence from cmfgen models. Issue 4 (18th February 2022) - Marcolino, W L F; Bouret, J -C; Rocha-Pinto, H J; Bernini-Peron, M; Vink, J S
ABSTRACT: Detailed knowledge about stellar winds and evolution at different metallicities is crucial for understanding stellar populations and feedback in the Local Group of galaxies and beyond. Despite efforts in the literature, we still lack a comprehensive, empirical view of the dependence of wind properties on metallicity ( Z ). Here, we investigate the winds of O and B stars in the Milky Way (MW) and Small Magellanic Cloud (SMC). We gathered a sample of 96 stars analysed by means of the nlte code cmfgen . We explored their wind strengths and terminal velocities to address the Z dependence, over a large luminosity range. The empirical wind–luminosity relation (WLR) obtained updates and extends previous results in the literature. It reveals a luminosity and Z dependence, in agreement with the radiatively driven wind theory. For bright objects (log  L / L ⊙ ≳ 5.4), we infer that $\dot{M} \sim Z^{0.5-0.8}$ . However, this dependence seems to get weaker or vanish at lower luminosities. The analysis of the terminal velocities suggests a shallow Z n dependence, with n ∼ 0.1−0.2, but it should be confirmed with a larger sample and more accurate V ∞ determinations. Recent results on SMC stars based on the PoWR code support our inferred WLR. On the other hand, recent bow-shocks measurements stand mostly above our derived WLR. Theoretical calculations of the WLR are not precise, specially at low L, where the results scatter. Deviations between our results and recent predictions are identified to be due to the weak wind problem and the extreme terminal velocities predicted by the models. The Z dependence suggested by our analysis deserves further investigations, given its astrophysical implications.